Systems approaches in public health: beyond mapping the causes - Loes Crielaard; Mary Nicolaou; Andrew D. Brown; S. Coosje Dijkstra; Fleur ter Ellen; Leonie K. Elsenburg; Angie Luna Pinzon; Wilma E. Waterlander; Karien Stronks (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Systems approaches are increasingly adopted in public health, commonly operationalised using system dynamics (SD). In public health, systems approaches have prioritised understanding the current system by describing the causes of a complex problem – e.g. obesity – as a system. It remains challenging to advance from understanding the current system producing undesired outcomes, towards responses to improve outcomes. Rather than creating models of the (entire) system, SD traditionally emphasises specific models to support policy development. While core concepts from SD have effectively been adopted in public health, there may be more to learn from SD when it comes to designing systems approaches that can fulfil the purpose of informing problem responses. Methods We reviewed seminal SD literature for clues on how to refine the focus of systems approaches, so that they lead to specific models supporting policy development. We conducted a narrative review, seeking a strategy that can be leveraged in systems approaches in public health. We concentrated on SD’s problem framing strategy, leading to two insights. Results Insight 1: Alongside the complex problem at stake (e.g. obesity), consider the intended result of the systems approach (coordination, learning, analysis or transformation). This helps recognise which system components are relevant to problem responses and make methodological decisions accordingly. Insight 2: If investigation of the current system reveals that only radical change can lead to improved outcomes, then proceed to envisioning how the system could be fundamentally transformed to support those desired outcomes. This next step helps to anticipate policy resistance, unintended consequences and counterintuitive behaviour by contemplating how the system would react due to proposed problem responses. Conclusions Applying a problem framing strategy, as is commonly done in SD, could make systems approaches in public health better positioned to inform problem responses. Problem framing stimulates the contribution of systems approaches to health policy, prioritising system components relevant to problem responses (Insight 1), which may not be part of the system (Insight 2).